2010
DOI: 10.1590/s0365-05962010000500015
|View full text |Cite
|
Sign up to set email alerts
|

Elastose perfurante serpiginosa em portadora da síndrome de Down

Abstract: Elastosis perforans serpiginosa is a rare, primary perforating dermatosis, frequently associated with certain genetic diseases and characterized by the transepidermal extrusion of elastic fibers. The present case report describes this dermatosis in a 19-year old female patient with Down's syndrome, who presented with asymptomatic erythematous, keratotic papules in an arciform pattern, located on her right forearm and knee, which had been present for five years. Following histopathological confirmation, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…1,11 Além da elastose dérmica a D-penicilamina pode induzir elastose sistémica, com dano às fibras elásticas das artérias, mucosa oral, trato respiratório superior, pulmão, ou endocárdio, gerando complicações potencialmente graves, como formações aneurismáticas e cistos pulmonares.…”
Section: Discussionunclassified
“…1,11 Além da elastose dérmica a D-penicilamina pode induzir elastose sistémica, com dano às fibras elásticas das artérias, mucosa oral, trato respiratório superior, pulmão, ou endocárdio, gerando complicações potencialmente graves, como formações aneurismáticas e cistos pulmonares.…”
Section: Discussionunclassified
“…That group of diseases also includes reactive perforating collagenosis, perforating folliculitis or Kyrle disease. In EPS, protrusions of altered elastic fibers and other connective tissue material through the papillary layer and epidermis (called transepithelial elimination) clinically manifest as small papules arranged in an annular pattern [1, 2]. …”
mentioning
confidence: 99%
“…In 1953, Lutz described the morphology of EPS and named it serpiginosa follicular keratosis . In 1955, Miescher showed that the extruded material contains elastin and suggested the term elastomer intrapapillare perforans veruciforme , which in 1958, Dammert and Putkonem changed into EPS [1, 2]. …”
mentioning
confidence: 99%
See 2 more Smart Citations